(untitled) (Balneo and PRM Research Journal, 2024)
Introduction: Stroke is a cerebrovascular disease with an impressive potential of disability, (multi)morbidity, and mortality among elderly patients. After stroke, a series of seque-lae represents a dynamic challenge for rehabilitation, especially for improving motor, cognitive and depressive disorders (1,2). Repetitive Transcranial Magnetic Stimulation (rTMS) is a non-invasive, painless, neuromodulations and neurostimulation method, which uses electromagnetic induction to administer repeated trains of pulses, with thera-peutic, diagnostic and research purposes (3–5). Method: We performed a systematic literature review of the related literature using a widely international accepted method - Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)(6), by searching, filtering, and selecting profile documen-tary material. Combinations/syntaxes of keywords were searched in the following interna-tional databases: Elsevier(7), PubMed(8), PMC(9), PEDro(10), in ISI indexed journals by Web of Knowledge/Science(11) during 1/01/2019-31/12/2021. Besides the 9 articles selected to enhance our related knowledge base we have also used some works freely identified in the literature. Results and discussions: 9 articles satisfied all the previous filtering criteria/ PRISMA steps and were selected for qualitative and detailed analysis. The benefits of rTMS, aiming to bring further insight into the responsiveness of motor deficit, depression, and cognitive impairment of the treatment, and through the favorable dynamic progress of the scores of the quantification scales used: HAMD-17/ HDRS, Hamilton Depression Scale; MMSE, Mini-Mental State Examination; MoCA, Montreal Cognitive Assesment; SCWT, Stroop Color-Word Interference Test; WAIS, Wechsler Adult Intelligence Scale; NIHSS, National Institutes of Health Stroke Scale; Barthel Index Score; ADL, Activities of Daily Living; mRS, modified Rankin Scale; FIM, Functional Independence Measures. Conclusions: Through this systematic review, we wish to present the perspective of the successful use of rTMS among elderly patients. We also intend for this work to be the start-ing point in the development of a doctoral study, which will include post-stroke sequelae, such as motor deficits, depressive and cognitive disorders, and through which we will strengthen scientific confidence in the tolerability and effectiveness of this type of stimula-tion for this segment of age.